Clathrin and LRP-1-independent constitutive endocytosis and recycling of uPAR. - Katia Cortese (Public Library of Science (PLoS), 2008)
Background The urokinase receptor (uPAR/CD87) is highly expressed in malignant tumours. uPAR, as a GPI anchored protein, is preferentially located at the cell surface, where it interacts with its ligands urokinase (uPA) and the extracellular matrix protein vitronectin, thus promoting plasmin generation, cell-matrix interactions and intracellular signalling events. Interaction with a complex formed by uPA and its inhibitor PAI-1 induces cell surface down regulation and recycling of the receptor via the clathrin-coated pathway, a process dependent on the association to LRP-1. Methodology/principal findings In this study, we have found that along with the ligand-induced down-regulation, uPAR also internalizes and recycles constitutively through a second pathway that is independent of LRP-1 and clathrin but shares some properties with macropinocytosis. The ligand-independent route is amiloride-sensitive, does not require uPAR partitioning into lipid rafts, is independent of the activity of small GTPases RhoA, Rac1 and Cdc42, and does not require PI3K activity. Constitutively endocytosed uPAR is found in EEA1 positive early/recycling endosomes but does not reach lysosomes in the absence of ligands. Electron microscopy analysis reveals the presence of uPAR in ruffling domains at the cell surface, in macropinosome-like vesicles and in endosomal compartments. Conclusions/significance These results indicate that, in addition to the ligand-induced endocytosis of uPAR, efficient surface expression and membrane trafficking might also be driven by an uncommon macropinocytic mechanism coupled with rapid recycling to the cell surface.